AN ARMY MARCHES ON ITS STOMACH: QUALITATIVE EVIDENCE ON FINANCIAL LITERACY AMONG MEMBERS OF THE MALAYSIAN ARMED FORCES - Nawi, Hafizah Mat; Hussin, Hafez Shahril; Salleh, Abdul Latif (International Journal of Psychosocial Rehabilitation, 2020)
: To date, personal financial mismanagement has been acknowledged as a fast-growing problem affecting many people globally in which it is particularly pervasive among the members of Malaysian Armed Forces (MAF). Therefore, this study was carried out to determine factors influencing the levels of financial literacy displayed by military personnel and impacts thereof. To this end, a model detailing the antecedents and consequences of financial literacy was developed. The study involved the implementation of semi-structured interviews with respondents engaged among the members of MAF. Data collection processes were initiated via interviews with 22 respondents including two experts, whereby the NVivo software was then employed to assign and group the interviewees’ comments and thematic analysis was implemented to analyse the data collected. The findings revealed the following information: a strong support for the proposed construct definition of financial literacy, identification of eight driving factors for the variable, financial inclusion as a moderating factor, and three perceived consequences of financial literacy. Furthermore, this study revealed additional items, which could be included in the existing constructs in order to expand the consequences of the focal construct. Following this, the research findings are instrumental for policymakers, military leaders, and those involved in developing and administering programmes geared towards improving personal financial management among military members. This is attributable to the goal set in the Five-Year Strategic Plan 2016-2020 for the Ministry of Defence Malaysia. Additionally, the findings elicited will also assist the Malaysian government in achieving the aspirations detailed in the National Strategy for Financial Literacy 2019-2023.